2020
DOI: 10.3847/2041-8213/ab6a9c
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Spatio-temporal Fragmentation in the Solar Flare Energy Release

Abstract: We analyzed a group of type III radio bursts and a Hα flare from the Sun that were observed simultaneously on 2015 January 14. The radio observations were in the spectral mode over the frequency range 85–35 MHz, and separately in the imaging mode at 80 MHz. The duration of the observations was ≈6 minutes. The centroids of the type III bursts and the Hα flare were independently scattered near the associated active region. But the displacements in the centroids of the two phenomenon are correlated with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Scattering of radio waves in the solar corona has been extensively studied since the first solar radio observations (Fokker 1965;Steinberg et al 1971;Steinberg 1972;Riddle 1974;Bougeret & Steinberg 1977;Robinson 1983;Bastian 1994;Arzner & Magun 1999;Thejappa et al 2007;Ramesh et al 2020). Consequently, Fokker (1965) performed the first numerical study of scattering on small-scale density inhomogeneities to estimate the apparent sizes and locations of solar radio-sources.…”
Section: Introductionmentioning
confidence: 99%
“…Scattering of radio waves in the solar corona has been extensively studied since the first solar radio observations (Fokker 1965;Steinberg et al 1971;Steinberg 1972;Riddle 1974;Bougeret & Steinberg 1977;Robinson 1983;Bastian 1994;Arzner & Magun 1999;Thejappa et al 2007;Ramesh et al 2020). Consequently, Fokker (1965) performed the first numerical study of scattering on small-scale density inhomogeneities to estimate the apparent sizes and locations of solar radio-sources.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beams injected onto a bundle of field lines propagate or are absorbed depending on the characteristics of the beams, the local plasma conditions, and the magnetic field geometry (Raoult et al, 1990;Reid and Kontar, 2015), so that an apparently simple type III burst observed with low spectral and temporal resolution is resolved into numerous bursts by more powerful instruments. Multiple sources in individual type III burst groups were found by Pick and Ji (1986) at meter wavelengths, spanning a typical angular width of 25 °(see also Pick and van den Oord, 1990;Paesold et al, 2001;Ramesh et al, 2020). The new VLA observations allowed for the first time to map the sources in detail and to determine subtelescopic sizes involved in the propagation.…”
Section: Evidence On Fragmented Energy Release and Particle Propagati...mentioning
confidence: 95%
“…The brightness temperature (T b ) of the contours 1 & 2, estimated using the 'beam' size of the GRAPH at 80 MHz, are ≈3×10 5 K. The 'dots' inside the contours in Figure 3 correspond to the centroids of some of the individual type I bursts (see Figure 4). We located them following the methodology described in Ramesh et al (2020a). Any ionospheric refraction effects on the radio source positions in the present case are expected to be very minimal since the observations were carried out close to the local noon during which time the zenith angle of the Sun is the least.…”
Section: Observationsmentioning
confidence: 99%